2023
DOI: 10.1021/acsnano.2c09752
|View full text |Cite
|
Sign up to set email alerts
|

An Antisense Oligonucleotide-Loaded Blood–Brain Barrier Penetrable Nanoparticle Mediating Recruitment of Endogenous Neural Stem Cells for the Treatment of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a neurodegenerative disease characterized by the death of dopaminergic (DA) neurons and currently cannot be cured. One selected antisense oligonucleotide (ASO) is reported to be effective for the treatment of PD. However, ASO is usually intrathecally administered by lumbar puncture into the cerebral spinal fluid, through which the risks of highly invasive neurosurgery are the major concerns. In this study, ZAAM, an ASO-loaded, aptamer Apt 19S-conjugated, neural stem cell membrane (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…To investigate the biocompatibility of MOC-O in major organs including the heart, liver, lungs and kidneys in mice, tissue samples were collected after two days of treatment and subjected to histological analysis using hematoxylin and eosin (H&E) staining. 2,36 As shown in Fig. 4A, all organs from the three groups exhibited uniform organization with no apparent signs of damage.…”
Section: Moc-o Protected Against Renal I/r Injurymentioning
confidence: 79%
See 1 more Smart Citation
“…To investigate the biocompatibility of MOC-O in major organs including the heart, liver, lungs and kidneys in mice, tissue samples were collected after two days of treatment and subjected to histological analysis using hematoxylin and eosin (H&E) staining. 2,36 As shown in Fig. 4A, all organs from the three groups exhibited uniform organization with no apparent signs of damage.…”
Section: Moc-o Protected Against Renal I/r Injurymentioning
confidence: 79%
“…Nonetheless, these bean-shaped organs are quite susceptible to various stressful conditions, particularly I/R injury, due to their high oxygen demand. 1,2 I/R injury is a common cause of kidney damage, often resulting from medical procedures such as kidney transplantation. This injury occurs when the blood supply to the kidneys is temporarily blocked, resulting in a lack of oxygen and nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Ti 2 C@BSA-ISO has acceptable therapeutic results compared to previous studies. 24,43,60 The long-held belief that titanium is inert and safe for human use can be seen as one of the main reasons for using titanium as an implant. 61 Compared to other elements (Mn, Cu), Ti 2 C@BSA-ISO has a safe composition and has a broader scope for disease treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, both groups were limited by the inability of their gapmers to cross the blood-brain barrier, requiring mutually exclusive treatment of either the CNS or peripheral muscles based on injection type. Interestingly, recent studies have identified numerous nanocarriers and apoptotic bodies which can successfully facilitate oligonucleotide penetration of the blood-brain barrier [65][66][67].…”
Section: Aso-mediated Androgen Receptor Knockdownmentioning
confidence: 99%